Macrobiont: Cradle for the Origin of Life and Creation of a Biosphere - Benton C. Clark; Vera M. Kolb (Life, 2020)
Although the cellular microorganism is the fundamental unit of biology, the origin of life (OoL) itself is unlikely to have occurred in a microscale environment. The macrobiont (MB) is the macro-scale setting where life originated. Guided by the methodologies of Systems Analysis, we focus on subaerial ponds of scale 3 to 300 m diameter. Within such ponds, there can be substantial heterogeneity, on the vertical, horizontal, and temporal scales, which enable multi-pot prebiotic chemical evolution. Pond size-sensitivities for several figures of merit are mathematically formulated, leading to the expectation that the optimum pond size for the OoL is intermediate, but biased toward smaller sizes. Sensitivities include relative access to nutrients, energy sources, and catalysts, as sourced from geological, atmospheric, hydrospheric, and astronomical contributors. Foreshores, especially with mudcracks, are identified as a favorable component for the success of the macrobiont. To bridge the gap between inanimate matter and a planetary-scale biosphere, five stages of evolution within the macrobiont are hypothesized: prebiotic chemistry → molecular replicator → protocell → macrobiont cell → colonizer cell. Comparison of ponds with other macrobionts, including hydrothermal and meteorite settings, allows a conclusion that more than one possible macrobiont locale could enable an OoL.